(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify: (linguistic security and its relationship with social thinking among female students in the intermediate stage). The sample consisted of (200) female students from the fourth grade of the intermediate stage / literary branch in schools affiliated with the General Directorate of Education in Baghdad (Karkh - Rusafa) for the academic year (2023-2024). To achieve the objectives of the research, the researcher relied on a linguistic security scale and prepared a scale for social thinking. After extracting the psychometric properties of both tools, the researcher applied them to the research sample and used appropriate statistical treatments. The results for the first objective showed a difference between the average scores of the research sample students in linguistic security, indicating that the research sample possesses linguistic security. The results for the second objective revealed a difference between the average scores of the research sample students in social thinking, indicating that the research sample possesses social thinking. Regarding the third objective, the Pearson correlation coefficient between linguistic security and social thinking was calculated, yielding a correlation coefficient of (0.68). To determine the significance of the relationship, the t-value of (13.07) was extracted, which is greater than the tabulated value of (1.96) at a significance level of (0.05). These results indicate a significant correlational relationship between linguistic security and social thinking in the research sample. In light of the research findings, the researcher recommended several recommendations and proposed a number of suggestions.